A facile acid treatment for P25 modification with enhanced photocatalytic H2 evolution – effect of Brønsted acid sites and oxygen vacancies. Issue 3 (3rd January 2020) - Lv, Chao; Lan, Xuefang; Li, Fuqiang; Wang, Lili; Xiao, Liqi; Wang, Cheng; Shi, Jinsheng; Yu, Shuguang
Abstract : Acid treated P25 catalysts (HP25- x, x represents the treatment temperature) were successfully fabricated via a simple soaking and drying process for photocatalytic H2 production. Abstract : Acid treated P25 catalysts (HP25- x, x represents the treatment temperature) were successfully fabricated via a simple soaking and drying process for photocatalytic H2 production. After acid treatment, a substantial number of –OH groups were obtained on the surface of HP25-60, which can act as Brønsted acid sites providing hydrogen protons for H2 generation. Besides, more oxygen vacancies and Ti 3+ sites were also created on the HP25-60 surface after acid treatment, which could enhance the carrier separation and transfer efficiency by capturing more electrons and holes, respectively. The H2 production over HP25-60 reached 4853 μmol h −1 with Pt as a co-catalyst, which is 7.1 times higher than 679 μmol h −1 of bare TiO2 . Three favorable factors for H2 photogeneration, i.e. Brønsted acid sites, oxygen vacancies and Ti 3+ sites, can be introduced on a catalyst surface via a simple one-step acid strategy, which can be applied as a universally-applicable modification method for valence-alternative metal oxide semiconductors for enhanced H2 photogeneration.